Rätoromanische Bibliographie Bibliografia retoromanza 1729-2010 - Videsott, Paul (20444cea-75ce-475a-895d-1a4b212a7914, 2011)
This bibliographic documentation follows the two comprehensive bibliographies on the Rhaeto-Romance language, the Rätoromanische Bibliographie (Maria Iliescu / Heidi Siller-Runggaldier) and the Rätoromanische Bibliographie 1985-1997 (Heidi Siller-Runggaldier / Paul Videsott). All data contained in these works have been integrated in this bibliography and updated until 2010. The nearly 5000 entries that cover a period from 1729 to 2010 are newly arranged according to subject areas and chronologically increasing publication dates. Consequently, this bibliography becomes a sort of "reading book of the history of science" representing the state of the art of international Rhaeto-Romance studies.